Nationalist character at Muhammadiyah school - Aulia, Syifa Siti; Arif, Dikdik Baehaqi; Sofihara, Idham; Utami, Astika Pungki; Laelaturrohmah, Laelaturrohmah; Arpannudin, Iqbal (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
One of the ways to strengthen nationalist character values is through formal education, including in Muhammadiyah schools. The practice needs strengthening in Muhammadiyah schools for deviations in student behavior that do not reflect the values of nationalist character. This article attempts to provide an overview of strengthening the values of nationalist characters through Muhammadiyah school culture. The research method used is qualitative research. The focus of the object in this study is strengthening the value of nationalist character for students in Muhammadiyah schools. The steps of data analysis using data reduction models, data presentation, conclusions. The study results show that there are several school programs to instill the values of nationalist character through school culture, among others, through learning in the classroom and habituation outside the classroom, among others, through extracurricular activities. The supporting factor is that the school establishes with the parties to run the program. The inhibiting factor is that some students are still not optimal in participating in a school program.